Embodied Technology: The Hybrid Cultural Materiality of the Tempayan in Hulu Sembakung - Afdil Hafidh; Puji Hastuti (Endogami: Jurnal Ilmiah Kajian Antropologi, 2026)
Technology in anthropological inquiry is not understood merely as an instrumental device, but rather as embodied materiality relations, movements, and meanings sedimented within an object. Drawing on Martin Heidegger’s notion of technology as enframing, this article explores the tempayan in the culture of the Hulu Sembakung community as a form of embodied technology enacted through ritual practices and social life. The tempayan emerges as a hybrid cultural materiality, the product of a historical synthesis between Chinese porcelain ceramics and local systems of meaning reproduced through ritual. Through the process of enframing, the tempayan is positioned as a ritual technology detached from the logic of its material origins, in contrast to the way porcelain is understood within Chinese culture. The Hulu Sembakung community engages in a process of revealing the tempayan through cultural rites that reinforce social cohesion, including within the context of cross-border relations. By employing a materiality-based approach across space and time, this article demonstrates how the mobility of the tempayan records historical networks and human movements that often diverge from the state’s territorial logic. Such mobility of cultural materiality generates friction with state materiality—that is, the state’s attempt to produce sovereignty through static territorial regulation. The findings of this article affirm that embodied cultural materiality, as exemplified by the tempayan in Hulu Sembakung, is capable of penetrating and unsettling the mythologised boundaries of sovereignty imposed by the state.